ANALYSIS OF SUPPORTING AND HINDER FACTORS IN IMPROVING HUMAN RESOURCE COMPETENCE AT PALANGKA RAYA UNIVERSITY - Nurlia Eka Damayanti; Dhina Sri Widyaningsih; Aprilita; Sanjayanto Nugroho; Olivia Winda Ony Panjaitan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study provides a concise overview of Palangka Raya University (UPR), a state university founded in 1963. UPR, operating as a Public Service Agency, has implemented strategic changes in response to financial management adjustments, particularly focusing on elevating the quality of higher education lecturers. The research evaluates UPR's performance over the last five years, resulting in the identification of five key business strategies. Examining UPR's human resources, the study outlines the organizational structure, emphasizing teaching staff and education personnel. In 2022, an analysis of lecturers' academic positions, space class, and gender distribution highlights the diversity within the university. Additionally, education personnel are scrutinized based on gender, age, years of service, and rank, providing a comprehensive insight into UPR's human resources landscape. Descriptive analysis pinpoints supporting factors, such as the competency certification process and research roadmaps, and inhibiting factors, including a lack of leadership synergy and lecturer awareness. Budgetary constraints, insufficient person-in-charge roles, and a lack of specific strategies are identified as obstacles. The research concludes with actionable recommendations to enhance human resource quality at UPR, emphasizing skills development, government support, reward systems, and the cultivation of professional attitudes and personality maturity. These strategies aim to foster a more productive and inclusive work environment in alignment with UPR's vision of producing competitive and morally grounded human resources.